2013
DOI: 10.1093/rheumatology/kes418
|View full text |Cite
|
Sign up to set email alerts
|

Gout, hyperuricaemia, sleep apnoea-hypopnoea syndrome and vascular risk

Abstract: Patients with gout and hyperuricaemia and suspicion of SAHS had polysomnographically confirmed SAHS in 88.9% of cases. These patients had more severe forms of SAHS and a greater prevalence of documented atherothrombotic disease compared with a control group with OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Most of these studies access a health database to form a risk ratio of the number of gout patients who have been diagnosed with OSA relative to those with no OSA diagnosis, ranging from 1.75:1 up to 3.7:1. They do not take into account the fact that a very large percentage of people with OSA have never been diagnosed with it [16], so they would have been misplaced in the no OSA diagnosis category instead of the diagnosed OSA category. If these studies had taken that into account, the estimated risk ratios of OSA with gout could have been much higher.…”
Section: Epidemiology and Clinical Studiesmentioning
confidence: 99%
“…Most of these studies access a health database to form a risk ratio of the number of gout patients who have been diagnosed with OSA relative to those with no OSA diagnosis, ranging from 1.75:1 up to 3.7:1. They do not take into account the fact that a very large percentage of people with OSA have never been diagnosed with it [16], so they would have been misplaced in the no OSA diagnosis category instead of the diagnosed OSA category. If these studies had taken that into account, the estimated risk ratios of OSA with gout could have been much higher.…”
Section: Epidemiology and Clinical Studiesmentioning
confidence: 99%
“…Epidemiological studies have suggested an association between gout and OSA. 4,5 Urate levels may be influenced by cell apoptosis secondary to apnoea-induced episodes of hypoxia. 6 Furthermore, increased adenosine triphosphate degradation in recurrent hypoxia may increase uric acid levels.…”
Section: Introductionmentioning
confidence: 99%